Biomechanical comparison of three different plate configurations for comminuted clavicle midshaft fracture fixation - UZER, GÖKÇER; Uzer, GÖKÇER; YILDIZ, FATİH; Yildiz, FATİH; BİLSEL, İSMAIL KEREM; BATAR, Suat; Bozdag, Ergun; Kuduz, Hacer; Bilsel, Kerem (My University, 2017)
Background: The aim of this study was to compare the fixation rigidity of anterior, anterosuperior, and superior plates in the treatment of comminuted midshaft clavicle fractures.